Late Life Disability and Experienced Wellbeing: Are Economic Resources A Buffer? - Freedman, Vicki A. (Disabil Health J, 2019)
BACKGROUND. Disablement has been linked to compromised wellbeing in later life, but whether material resources buffer these negative effects is unclear. OBJECTIVE/HYPOTHESIS. Drawing upon conceptual models of stress and coping, we analyze experienced wellbeing data from time diary interviews with adults ages 60 and older. We expect that experienced wellbeing will be influenced by each stage of the disablement process and that higher income and wealth will buffer the negative effects of disability on experienced wellbeing. Because income is a better reflection of one’s liquid resources while assets reflect lifetime accumulation, we expect income to be a more substantial buffer than assets. METHODS. We use the Disability and Use of Time Supplement to the Panel Study of Income Dynamics (N=1607). We consider several measures of the disablement process (activity limitations, impairment severity, duration of limiting condition) and history of work limitation and evaluate both pre-tax income and net worth quartiles. We estimate a series of multi-level regression models that account for clustering of individuals within couples. We calculate the marginal effects of disability on wellbeing at different quartiles of economic resources. RESULTS. We find that impairment severity is associated with worse experienced wellbeing before and after adjusting for covariates, and income buffers these negative effects for those in the middle-income quartiles. CONCLUSIONS. Future research should further explore the mechanisms through which income buffers the negative effects of impairment severity and specify the accommodations that enable economically disadvantaged and advantaged older adults alike to withstand physical declines while maintaining wellbeing.